Relationship between Ultrasound Attenuation and Specific Gravity of Timber - Sanyal, S. N.; Pandey, C. N. (Indian Forester, 1978)
In this Paper an endeavour has been made to establish simple relationship between ultrasound attenuation and specific gravity at a particular moisture content (as for as practicable) for various timber speeimens. As such from this relation by measuring the ultrasound attenuation quality of the material can be easily estimated in situ.